2021
DOI: 10.1093/restud/rdab020
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in the Hot Hand Fallacy: Detecting Streaky Alternatives to Random Bernoulli Sequences

Abstract: We study a class of permutation tests of the randomness of a collection of Bernoulli sequences and their application to analyses of the human tendency to perceive streaks of consecutive successes as overly representative of positive dependence—the hot hand fallacy. In particular, we study permutation tests of the null hypothesis of randomness (i.e., that trials are i.i.d.) based on test statistics that compare the proportion of successes that directly follow k consecutive successes with either the overall prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Our results tie together multiple themes from previous research into the hot hand hypothesis in basketball. First, our results align with those from controlled shooting experiments which find a hot hand, such as Miller & Sanjurjo (2018)'s paradigmshifting article on the hot hand and gambler's fallacy, despite the power issues pointed out by Ritzwoller & Romano (2022). Our finding that the existence of a hot hand for shots within the same location also provides support for previous papers which find a hot hand in NBA free throw shooting (e.g., Arkes, 2010;Lantis & Nesson, 2021).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results tie together multiple themes from previous research into the hot hand hypothesis in basketball. First, our results align with those from controlled shooting experiments which find a hot hand, such as Miller & Sanjurjo (2018)'s paradigmshifting article on the hot hand and gambler's fallacy, despite the power issues pointed out by Ritzwoller & Romano (2022). Our finding that the existence of a hot hand for shots within the same location also provides support for previous papers which find a hot hand in NBA free throw shooting (e.g., Arkes, 2010;Lantis & Nesson, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…After correcting for this bias, the original data in Gilovich et al (1985) support the existence of a hot hand. However, Ritzwoller & Romano (2022) develop new tests for evaluating the proportion of successes following consecutive successes with either the overall proportion of successes or the proportion of successes following consecutive failures. Applying their tests to the Gilovich et al (1985) controlled shooting experiment data, they find that the hot hand found by Miller & Sanjurjo (2018) is driven by only one shooter.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(2006) consider the application of permutation testing as a method of testing for periodicity in biological data. In a more theoretical setting, Jentsch and Pauly (2015) use randomization methods to test equality of spectral densities, and Ritzwoller and Romano (2020) consider permutation testing in the setting of dependent Bernoulli sequences.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of time series data, Nichols and Holmes (2002) discuss the application of permutation testing to neuroimaging data, and Ptitsyn et al (2006) consider the application of permutation testing as a method of testing for periodicity in biological data. In a more theoretical setting, Jentsch and Pauly (2015) use randomization methods to test equality of spectral densities, and Ritzwoller and Romano (2020) consider permutation testing in the setting of dependent Bernoulli sequences.…”
Section: Introductionmentioning
confidence: 99%